As relações de trabalho e a resistência escrava em Sant'Ana de Paranaíba: província de Mato Grosso (1828- 1888) - Camargo, Isabel Camilo [UNESP] (2015)
This work aims to analyze how was the relationship between holders and slaves in Sant'Ana de Paranaíba in the nineteenth century and to discuss their sociabilities. During this period, Sant'Ana de Paranaíba belonged to the province of Mato Grosso and was a stopping point and gateway to people coming and going of the provinces of Minas Gerais and São Paulo towards Cuiabá and Goiás. Today, the locality would amount to a part of the east of the current state of Mato Grosso do Sul. The use of black slaves as labor occurred since the eighteenth century in the monções, but it was the occupation of entrants in the location that was effective the setting of slaves in the region. Among the topics discussed in the thesis we can cite a historiographical debate about Brazilian slavery, a study on the occupation of Sant'Ana de Paranaíba and the influence of the patriarchal family to the formation of local society. We tried to find the slave in various historical sources as manumission letters, the Emancipation Fund List of 1874, civil proceedings and criminal processes. Treading a path for the Social History seek to examine not only free and slaves men, but also free and slaves women and children